Gene expression elucidates functional impact of polygenic risk for schizophrenia - Fromer, Menachem; Roussos, Panos; Sieberts, Solveig K; Johnson, Jessica S; Kavanagh, David H; Perumal, Thanneer M; Ruderfer, Douglas M; Oh, Edwin C; Topol, Aaron; Shah, Hardik R; Klei, Lambertus L; Kramer, Robin; et al. (Nature neuroscience, 2016)
The CommonMind Consortium sequenced RNA from dorsolateral prefrontal cortex of subjects with schizophrenia ( N = 258) and control subjects ( N = 279), creating a resource of gene expression and its genetic regulation. Using this resource, they found that ∼20% of schizophrenia loci have variants that may contribute to altered gene expression and liability. Over 100 genetic loci harbor schizophrenia-associated variants, yet how these variants confer liability is uncertain. The CommonMind Consortium sequenced RNA from dorsolateral prefrontal cortex of people with schizophrenia ( N = 258) and control subjects ( N = 279), creating a resource of gene expression and its genetic regulation. Using this resource, ∼20% of schizophrenia loci have variants that could contribute to altered gene expression and liability. In five loci, only a single gene was involved: FURIN , TSNARE1 , CNTN4 , CLCN3 or SNAP91 . Altering expression of FURIN , TSNARE1 or CNTN4 changed neurodevelopment in zebrafish; knockdown of FURIN in human neural progenitor cells yielded abnormal migration. Of 693 genes showing significant case-versus-control differential expression, their fold changes were ≤ 1.33, and an independent cohort yielded similar results. Gene co-expression implicates a network relevant for schizophrenia. Our findings show that schizophrenia is polygenic and highlight the utility of this resource for mechanistic interpretations of genetic liability for brain diseases.